Dynamic performances of multi-renewable energy sources in a microgrid during islanding operation - Piyadanai Pachanapan (2020)
© 2020, Greater Mekong Subregion Academic and Research Network, Asian Institute of Technology. The dynamic performances of a microgrid system with multi-renewable energy sources, during the islanding condition, are presented in this paper. The test system consists of a small-scale hydro generator, photovoltaic (PV) system and battery energy storage system. In addition, the hydro generator is using the synchronous machine; while PV and battery systems are interfaced with the grid through power converters. The study aims to demonstrate the performance of islanding operation in a very light load condition, in which the total power generation from energy sources is extremely higher than the total demand. Three different control strategies are examined, which depending on technologies and functionalities of available energy sources in the system. The performance of each control strategy is simulated by using the transient simulation on DIgSILENT PowerFactory software. The simulation results illustrate that, in the islanding mode, the cooperated controls among hydro generator, PV and battery can deal with the changes of frequency and voltage during the islanding condition effectively. Additionally, the active power curtailment of hydro generator and PV system is required for this solution to restrict the power production, especially in the light load condition. Moreover, the Volt-Var supported by PV and battery systems can provide a fast voltage controllability during the islanding operation.